Comparison of intensity modulated radiotherapy (IMRT) with intensity modulated particle therapy (IMPT) using fixed beams or an ion gantry for the treatment of patients with skull base meningiomas - Kosaki, Katsura; Ecker, Swantje; Habermehl, Daniel; Rieken, Stefan; Jäkel, Oliver; Herfarth, Klaus; Debus, Jürgen; Combs, Stephanie (Radiation oncology, 2012)
To examine the potential improvement in treatment planning for patients with skull base meningioma using IMRT compared to carbon ion or proton beams with and without a gantry.